2022
DOI: 10.3390/nano12071223
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nanostructures Based on Perylene Diimide Bioconjugates: From Self-Assembly to Applications

Abstract: Self-assembling π-conjugated systems constitute efficient building blocks for the construction of supramolecular structures with tailored functional properties. In this context, perylene diimide (PDI) has attracted attention owing to its chemical robustness, thermal and photo-stability, and outstanding optical and electronic properties. Recently, the conjugation of PDI derivatives to biological molecules, including oligonucleotides and peptides, has opened new avenues for the design of nanoassemblies with uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…Numerous bioelectronic devices are composed of π-conjugated organic semiconducting nanomaterials, which allow very effective charge transfer . Among π-conjugated systems, perylene diimide (PDI)-derived molecules have received a great deal of attention for their optoelectronic, physicochemical, and/or structural properties that can be modulated by the modification of their substituents. , In addition to their chemical robustness and thermal stability, PDIs are known for their propensity to self-assemble into diverse supramolecular architectures that modulate their spectroscopic and semiconductive properties. While PDI self-assembly is mainly driven by π–π stacking interactions, it can be dramatically altered by environmental conditions, such as solvent polarity, pH, concentration, and temperature as well as the chemical nature and position of their substituents .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous bioelectronic devices are composed of π-conjugated organic semiconducting nanomaterials, which allow very effective charge transfer . Among π-conjugated systems, perylene diimide (PDI)-derived molecules have received a great deal of attention for their optoelectronic, physicochemical, and/or structural properties that can be modulated by the modification of their substituents. , In addition to their chemical robustness and thermal stability, PDIs are known for their propensity to self-assemble into diverse supramolecular architectures that modulate their spectroscopic and semiconductive properties. While PDI self-assembly is mainly driven by π–π stacking interactions, it can be dramatically altered by environmental conditions, such as solvent polarity, pH, concentration, and temperature as well as the chemical nature and position of their substituents .…”
Section: Introductionmentioning
confidence: 99%
“…34 Moreover, in this area of research, a recent review by Bourgault and coworkers demonstrated supramolecular-nanostructural behavior and self-assembly applications of PDI-based-bioconjugate materials. 35 Functionalized and non-functionalized PDI-derivatives are rarely explored in the design and characterization of hyperbranched polymers. So far there has only been three examples of such reported polymers, which mainly focuses on the synthesis of PDI-chromophore incorporated hydrophilic branched polymer matrix or HBCPs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] In the case of conjugated molecules that have a great stacking tendency in solution, accurate control of their supramolecular oligomerization through face-to-face stacking in one-dimensional (1D) space is highly valuable, because it has been well established that the stacking of conjugated systems can lead to new photoluminescence properties that are not available through single molecules, but largely related to the degree of stacking-based aggregation or polymerization. 4,[11][12][13][14][15] Currently, the self-assembly of the most simplest dimers 4,16,17 and more complicated 1D supramolecular polymers, 4,12 which are the start and end points of supramolecular polymerization, by a variety of conjugated systems has been reported. In many cases, their stacking-caused photoluminescence behaviours have been revealed to be remarkably different from those of single monomers.…”
Section: Introductionmentioning
confidence: 99%